2016
DOI: 10.20937/rica.2016.32.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Mineralización De Etilenglicol Por Foto-Fenton Asistido Con Ferrioxalato

Abstract: Palabras clave: agua residual de la industria de pinturas, ion ferroso, peróxido de hidrógeno, ion oxálico RESUMEN Se evaluó la efectividad del proceso foto-Fenton asistido con ferrioxalato para la mineralización de 1000 mg/L de etilenglicol presente en agua destilada y en agua residual proveniente de una planta de producción de pinturas. Se observó que la eficiencia de mineralización del etilenglicol es función de las concentraciones iniciales de ion ferroso, oxalato y peróxido de hidrógeno. Los mayores nivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Together with the extremely low amounts of iron that leached through the photoreactions (< 2 %), this fact points to the high stability of this material synthetized by sol-gel method and studied in this work. Although encouraging values were obtained in the percentages of degradation of EG in the photo-Fenton heterogeneous system, the obtained results in our previous investigation of EG degradation in a homogeneous system [1] revealed that the best removal efficiencies for EG are reached using a ferrioxalate-induced photo-Fenton system. Thus, the highest level of degradation (90 %) was obtained using 10 mg/L of Fe 2+ , 150 mg/L of C 2 O 4 2and 500 mg/L of H 2 O 2 after 3 h of UV artificial irradiation.…”
Section: Photocatalytic Performancementioning
confidence: 72%
See 2 more Smart Citations
“…Together with the extremely low amounts of iron that leached through the photoreactions (< 2 %), this fact points to the high stability of this material synthetized by sol-gel method and studied in this work. Although encouraging values were obtained in the percentages of degradation of EG in the photo-Fenton heterogeneous system, the obtained results in our previous investigation of EG degradation in a homogeneous system [1] revealed that the best removal efficiencies for EG are reached using a ferrioxalate-induced photo-Fenton system. Thus, the highest level of degradation (90 %) was obtained using 10 mg/L of Fe 2+ , 150 mg/L of C 2 O 4 2and 500 mg/L of H 2 O 2 after 3 h of UV artificial irradiation.…”
Section: Photocatalytic Performancementioning
confidence: 72%
“…Ethylene glycol (EG) is widely used in numerous industrial applications such as solvent in the paint and plastic industries, in some skin lotions and flavoring essences and also as deicing fluid for airport run ways and antifreeze agent in cooling systems [1][2][3][4]. Typical concentrations of EG in industrial wastewater scan can be in the 25-250 g/L range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review on photocatalysis [27] describes generation of singlet oxygen and its role in the photo-oxygenation (incorporation of molecular oxygen into molecules), combination of photochemical processes with enzyme catalysis, application of continuous flows or microreactors for their optimization. Some examples of such reactions are the synthesis of N-containing heterocycles by photo-oxidation of furan derivatives, asymmetric oxidations catalysed with enzymes, and preparation of several F-organic compounds by photocatalysed trifluoromethylation of aromatics, using photocatalysis booth and reactors described in [28].…”
Section: General Synthesis Methods Of Green Chemistrymentioning
confidence: 99%
“…Among various applications of GC, great advantages derive from the employment of water and other green solvents in chemical reactions such as aqueous catalysis [ 34 , 35 , 36 ], of supercritical fluids (i.e., supercritical CO 2 ) [ 37 , 38 ], ionic liquids (ILs) [ 39 , 40 , 41 ], deep eutectic solvents (DES) [ 42 , 43 , 44 ] and fluorous media [ 45 ]. Other green approaches are microwave-assisted and ultrasound-assisted processes [ 46 , 47 , 48 ], hydro/solvo thermal reactions [ 49 , 50 ], magnetic field-assisted synthesis [ 51 ], mechanochemistry [ 52 ], and UV irradiation [ 53 , 54 ]. All these approaches and the evolution of GC have been accurately reviewed [ 1 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], highlighting that over the last 20 years, the principles of green chemistry have strengthened the environmental sustainability of chemical processes.…”
Section: Green Chemistrymentioning
confidence: 99%